Peran Pendidikan Anti Korupsi Dalam Meningkatkan Kesadaran Hukum Dan Membentuk Karakter Mahasiswa Di Perguruan Tinggi - Annisa Septiani; Nathasya Fithasari (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Corruption is a serious problem that requires early prevention efforts through education. Higher education institutions play a crucial role in instilling anti-corruption values in students. This study aims to analyze the role of anti-corruption education in enhancing legal awareness and shaping the character of students in higher education institutions. The method used is a qualitative approach through interviews and literature review. The results show that anti-corruption education plays a role in fostering students’ legal understanding and values of integrity, although its implementation is not yet optimal. Therefore, strengthening the implementation of anti-corruption education is necessary to make it more effective in shaping students of integrity